Guidance Note for Article IV Consultations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This note provides guidance to staff on the conduct of surveillance in the context of Article IV consultations, a core activity of the Fund. Surveillance involves the continuous monitoring of members' economic and financial policies and their impact on their own and global stability. During Article IV consultations, staff holds pointed discussions with country authorities on the economic situation, the authorities' policies and how these affect the country's stability, the role of potential or actual spillovers where relevant, and desirable policy adjustments. These discussions are then reported to the Fund's Executive Board for its consideration. The goal, through thorough analysis, candid discussions, and a peer-review mechanism, is to promote the stability of members' economies, as well as the effective operation of the international monetary system, including through maintaining global stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet